2005
DOI: 10.1007/s10654-004-6515-6
|View full text |Cite
|
Sign up to set email alerts
|

Anemia as a risk factor for infectious diseases in infants and toddlers: Results from a prospective study

Abstract: Anemia due to iron deficiency is the most prevalent form of micronutrient malnutrition in the world, however, the causal relationship between anemia and infection remains unclear. We examined prospectively, the association between anemia and infection among Bedouin infants. We recruited 293 families and newborns from the Bedouin population, which is ongoing major lifestyle changes, during the periods of 1989-1992 and 1994-1997 and followed them to age 18 months. The number of diarrhea and respiratory disease e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 35 publications
3
44
2
3
Order By: Relevance
“…Diarrhea during childhood, even of moderate severity, has been associated to lower iron absorption and consequent reduction in hemoglobin concentration. 11 With regard to parasitic diseases studies with infants conducted by Batista Filho & Ferreira 3 (1996) found no association with iron defi ciency anemia in the Northeastern region.…”
Section: Discussionmentioning
confidence: 98%
“…Diarrhea during childhood, even of moderate severity, has been associated to lower iron absorption and consequent reduction in hemoglobin concentration. 11 With regard to parasitic diseases studies with infants conducted by Batista Filho & Ferreira 3 (1996) found no association with iron defi ciency anemia in the Northeastern region.…”
Section: Discussionmentioning
confidence: 98%
“…Observação semelhante foi apontada para crianças de 6 a 59 meses do Timor Leste 32 , onde menores valores de hemoglobina sanguínea foram verificados em crianças com relato de diarréia nas últimas duas semanas prévias ao estudo. O aumento no risco de anemia com aumento de infecções diarréicas e respiratórias também foi verificado por Levy et al 33 , em estudo prospectivo com beduínos de 18 meses. De acordo com Beresford et al 34 , a diarréia pode ocasionar perda sanguínea intestinal e a ocorrência recente dessa infecção tem sido sugerida como um marcador de episódios mais freqüentes e persistentes.…”
Section: Discussionunclassified
“…37 Infant anemia has been associated with infectious gastrointestinal and respiratory morbidity in young infants from a developing country, even after controlling for environmental and socioeconomic factors. 38 The identification of anemia at birth as a risk factor for neonatal infections reinforces the need for close monitoring of hemoglobin values among infants of HIV-1-infected mothers, especially those whose mothers received antiretroviral drugs during pregnancy.…”
Section: Discussionmentioning
confidence: 99%